Distributed Denial of Service (DDoS) framework in Software-Defined Networking (SDN): a comprehensive review, challenges and future directions / Kanqi Xie ... [et al.] - Kanqi, Xie; Darus, Mohamad Yusof; Boxun, Liao; Nan, Ding; Ramli, Azlin (Universiti Teknologi MARA, 2025)
Distributed Denial of Service (DDoS) attacks represent a major threat to network security.. In response, this paper examines the potential of countering DDoS attacks through the integration of Software-Defined Networking (SDN). SDN separates the network control logic from the underlying routers and switches, which facilitates the communication between software components. Moreover, the synergy of SDN with Machine Learning (ML) and Deep Learning (DL) technologies provide a promising approach for effective threat mitigation. This systematic review explores the evolving landscape of information security defense frameworks within the context of Internet of Things (IoTs) security. Over the past five years, numerous articles have contributed to the understanding of SDN based DDoS defense architecture. This review encompasses various aspects, including the design of SDN based DDoS frameworks, implementation steps, data analysis methods, DDoS data sources, and application scenarios of defense frameworks. Performance and characteristics of different defense technologies are analyzed, addressing common challenges in the research field. This study provides a valuable reference for researchers to develop efficient and reliable DDoS defense frameworks in SDN mode.